No evidence for age-related differences in mitochondrial RNA quality in the female germline. Issue 3 (16th September 2022) - Hartley, Fiona; Alageel, Arwa; Appeltant, Ruth; Gray, Nicki; Repapi, Emmanouela; Wells, Dagan; Williams, Suzannah A; Poulton, Joanna
Abstract : Graphical abstract: Abstract: Mitochondrial quality is implicated as a contributor to declining fertility with aging. We investigated mitochondrial transcripts in oocytes and their associated cumulus cells from mice of different ages using RNA-seq. Mice aged 3 weeks, 9 weeks, and 1 year were superovulated, and 48 h later, oocyte cumulus complexes were collected by follicle puncture. We did not detect any major differences that could be attributed to aging. However, mitochondrial RNA transcripts which deviated from the consensus sequence were found at a higher frequency in cumulus cells than in their corresponding oocyte. Previous investigations have shown that variation in the sequence of mtRNA transcripts is substantial, and at least some of this can be accounted for by post-transcriptional modifications which impact base calling during sequencing. Our data would be consistent with either less post-transcriptional modification in mitochondrial RNA from oocytes than cumulus cells or with lower mtDNA mutational load. Lay summary: Women become less fertile as they age. Shortage of energy contributes to this, caused by a decline in the quality of mitochondria (the powerhouses of the cell) in the egg. Genes are the blueprint for the cell. They are made of DNA which is copied into an RNA message, or instructions, for making proteins. We counted differences in the RNA message of developing eggs and the cells that support them during development (cumulus cells). We compared the number of these differences in mice of different ages. These age groups represent mice had not reached puberty, those of prime reproductive age, and old mothers. We did not find any differences linked to the age of the mice. However, we did find differences between the egg and the cumulus cells. In most cases, there were lower levels of mutations in eggs than there were in cumulus cells.